(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2020)
The article presents a concise review of political criticism through the medium of humor and satire, at the time of ex-Yugoslavia and during its dissolution. It covers several important magazines and individual authors from ex-Yugoslav republics that, in difficult times for the freedom of speech, have shown dignity and courage to describe, criticize and warn regarding existing nationalisms and the futility of wars. Today their works have not only artistic but also historical and anthropological importance since they speak, more fluently than the official and often censored history, about the time in which they were created, and the circumstances in which the voices of reason were suppressed.